Mechanisms of Salmonella Attachment and Survival on In-Shell Black Peppercorns, Almonds, and Hazelnuts - Li, Ye; Salazar, Joelle K.; He, Yingshu; Desai, Prerak; Porwollik, Steffen; Chu, Weiping; Paola, Palma-Salgado Sindy; Tortorello, Mary Lou; Juarez, Oscar; Feng, Hao; McClelland, Michael; Zhang, Wei (Frontiers in Microbiology, 2020)
Salmonella enterica subspecies I (ssp 1) is the leading cause of hospitalizations and deaths due to known bacterial foodborne pathogens in the United States and is frequently implicated in foodborne disease outbreaks associated with spices and nuts. However, the underlying mechanisms of this association have not been fully elucidated. In this study, we evaluated the influence of storage temperature (4oC or 25oC), relative humidity (20% or 60%), and food surface characteristics on the attachment and survival of five individual strains representing S. enterica ssp I serovars Typhimurium, Montevideo, Braenderup, Mbandanka, and Enteritidis on raw in-shell black peppercorns, almonds, and hazelnuts. We observed a direct correlation between the food surface roughness and S. enterica ssp 1 attachment; and significant inter-strain difference in survival on the shell surface under various storage conditions. A combination of low relative humidity (20%) and ambient storage temperature (25oC) resulted in the most significant reduction of S. enterica on shell surface (p<0.05). To identify genes potentially associated with S. enterica attachment and survival on shell surface, we inoculated a library of 120,000 random transposon insertion mutants of an S. Enteritidis strain on almond shells, and screened for mutant survival after 7 days of storage at 20% relative humidity and 25oC. Mutants in 155 S. Enteritidis genes which are involved in carbohydrate metabolic pathways, aerobic and anaerobic respiration, inner membrane transport, and glutamine synthesis displayed significant selection on almond shells (p<0.05). Findings of this study suggest that various food attributes, environmental factors and an unexpectedly complex metabolic and regulatory network in S. enterica ssp 1 collectively contribute to the bacterial attachment and survival on low moisture shell surface, providing new data for the future development of knowledge-based intervention strategies.